Sports clusters as a perspective way to develop the sports industry - Durdieva K.Kh; Mirzaliyeva Sh.E; Ismagulova G.N. (Genius Journals, 2023)
Sports clusters today are a popular and up-to-date trend in terms of its high potential for sports industry development. However, along with the advantages these provide, the sports sector development is also to a certain extent restrained due to a number of factors. Within the framework of the article, the worldwide use and implementation of sports clusters having high potential for sports industry development and sports cluster is a comprehensively studied
Keywords: sports clusters; sports industry; physical culture